2015
DOI: 10.1002/nvsm.1526
|View full text |Cite
|
Sign up to set email alerts
|

Volunteerism, compassion and religiosity as drivers of donations practices

Abstract: The topic of donations is one of high relevance and has been widely covered in contemporary marketing literature. It is a topic of interest to both theoreticians and practitioners alike, particularly due to its implicit links to fundraising activities and research. The reality of what makes an individual donor ultimately part with his money and give it away to a nonprofit organization is a hot contemporary topic. This study looks into the role of religiosity as a predictor of donations practices. Also voluntee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
25
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 24 publications
(28 citation statements)
references
References 81 publications
(132 reference statements)
2
25
0
1
Order By: Relevance
“…In a more recent study, Ranganatham and Henley () found that religiosity did positively impact charitable intentions but no such effect was found for AHO. Based on this review, and given that the “common rule” (de Abreu et al, ) among all major religions is helping others, we offer the following hypotheses:H2 The relationship between religiosity and charitable giving is mediated by AHO.H3 The relationship between religiosity and charitable giving is mediated by ACO.…”
Section: Theoretical Backgroundmentioning
confidence: 99%
See 4 more Smart Citations
“…In a more recent study, Ranganatham and Henley () found that religiosity did positively impact charitable intentions but no such effect was found for AHO. Based on this review, and given that the “common rule” (de Abreu et al, ) among all major religions is helping others, we offer the following hypotheses:H2 The relationship between religiosity and charitable giving is mediated by AHO.H3 The relationship between religiosity and charitable giving is mediated by ACO.…”
Section: Theoretical Backgroundmentioning
confidence: 99%
“…All of the world's major religions encourage helping others (de Abreu, Laureno, da Silva, & Duionisio, ; Norenzayan & Shariff, ; Ranganatham & Henley, ). The Old Testament (Jewish) of the bible in Deuteronomy 15:11 says “For there will never cease to be poor in the land.…”
Section: Theoretical Backgroundmentioning
confidence: 99%
See 3 more Smart Citations